Metabolic Engineering of Histidine Kinases in Clostridium beijerinckii for Enhanced Butanol Production - Xin, Xin; Cheng, Chi; Du, Guangqing; Chen, Lijie; Xue, Chuang (Frontiers in Bioengineering and Biotechnology, 2020)
Clostridium beijerinckii, a promising industrial microorganism for butanol production, suffers from low butanol titer and lack of high-efficiency genetical engineering toolkit. A few histidine kinases (HKs) responsible for Spo0A phosphorylation have been demonstrated as functionally important components in regulating butanol biosynthesis in solventogenic clostridia such as C. acetobutylicum, but no study about HKs has been conducted in C. beijerinckii. In this study, six annotated but uncharacterized candidate HK genes sharing partial homologies (no less than 30%) with those in C. acetobutylicum were selected based on sequence alignment. The encoding region of these HK genes were deleted with CRISPR-Cas9n-based genome editing technology. The deletion of cbei2073 and cbei4484 resulted in significant change in butanol biosynthesis, with butanol production increased by 40.8 and 17.3% (13.8 g/L and 11.5 g/L vs. 9.8 g/L), respectively, compared to the wild-type. Faster butanol production rates were observed, with butanol productivity greatly increased by 40.0 and 20.0%, respectively, indicating these two HKs are important in regulating cellular metabolism in C. beijerinckii. In addition, the sporulation frequencies of two HKs inactivated strains decreased by 96.9 and 77.4%, respectively. The other four HK-deletion (including cbei2087, cbei2435, cbei4925, and cbei1553) mutant strains showed few phenotypic changes compared with the wild-type. This study demonstrated the role of HKs on sporulation and solventogenesis in C. beijerinckii, and provided a novel engineering strategy of HKs for improving metabolite production. The hyper-butanol-producing strains generated in this study have great potentials in industrial biobutanol production.